SPATA2 suppresses epithelial‐mesenchymal transition to inhibit metastasis and radiotherapy sensitivity in non–small cell lung cancer via impairing DVL1/β‐catenin signaling. Issue 11 (22nd February 2023) - Ji, Hongbo; Zhang, Lu; Zou, Man; Sun, Yanchen; Dong, Xiaohan; Mi, Zeyun; Meng, Maobin; Yuan, Zhiyong; Wu, Zhiqiang
Abstract: Metastasis is the major cause of cancer‐related death of cancer patients. Epithelial‐mesenchymal transition (EMT) is one critical process during the cascade of tumor metastasis. EMT is a developmental program exploited by cancer cells to transition from epithelial state to mesenchymal state and confers metastatic properties as well as treatment resistance. Finding factors to inhibit EMT will greatly improve the prognosis patients. Spermatogenesis associated 2 (SPATA2) was originally isolated from human testis and proved playing a role in spermatogenesis. To date, however, the role of SPATA2 in oncogenesis is unknown. In the current study, by mining the public database and validating in a cohort of collected non–small cell lung cancer (NSCLC) specimens, we uncovered that the expression of SPATA2 positively correlated with the prognosis of patients and was an independent prognosis marker in NSCLC. Functional studies proved that ectopic overexpression of SPATA2 inhibited EMT resulting in impaired motility and invasiveness properties in vitro and metastasis in vivo, and increased radiosensitivity in NSCLC. Mechanistic investigation showed that SPATA2 could suppress the β‐catenin signaling via attenuating DVL1 ubiquitination to achieve the functions. Taken together, the current study revealed an inhibitory role of SPATA2 on EMT and that SPATA2 could be a potential target for therapy of NSCLC. Abstract : Spermatogenesis associated 2 (SPATA2) inhibited epithelial‐mesenchymal transition leading to impaired metastasis and increased radiosensitivity in non–small cell lung cancer. Mechanistic investigation revealed that SPATA2 binds with CYLD and enhanced CYLD deubiquitinase activity to reduce K63‐linked polyubiquitination of DVL1, which results in DVL1 degradation and subsequently attenuating β‐catenin signaling.